Fundamental Rules Related to What is Forbidden a Contemporary Applied Fundamentalist Study - Jaber, Saleh Mahmoud Saleh (Dirasat: Shari’a and Law Sciences, 2024)
Objectives: This study addressed some of the fundamental principles related to what is prohibited (haram). Its aim is to elucidate the reality of the foundational principles related to what is prohibited, focusing specifically on the most important foundational principles related to what is prohibited, explaining their overall meaning and types of what is prohibited, and highlighting the role and impact of foundational principles in contemporary applications. Methods: In this research, a descriptive-analytical methodology based on induction was adopted. Scientific material was collected, categorized, and analyzed according to the principles of scientific research to ultimately arrive at appropriate solutions that align with the requirements of our era without contradicting the principles of our tolerant Sharia. Results: The study reached several results, among the most prominent being the clarification of the reality of the foundational principles related to what is prohibited as a holistic issue related to what is forbidden. It was revealed that the principles related to what is prohibited are not limited to five rules discussed in the research. Additionally, it was found that what is prohibited has types, including what is prohibited by origin and what is prohibited by description. Furthermore, the study highlighted the role and impact of foundational principles in contemporary applications. Conclusion: The theoretical aspect was highlighted in contemporary practical applications in several instances, including (voluntary abortion), (working in commercial insurance companies), (inheritance of shares of prohibited companies), (margin trading of currencies), and (trading mixed stocks).